American law in a global context - Fletcher, George P. (Oxford University Press, 2005)
American Law in a Global Context is an elegant and erudite introduction to the American legal system from a global perspective. It covers the law and lawyering tools taught in the first year of law school, explaining the underlying concepts and techniques of the common law used in U.S. legal practice. The ideas central to the development and practice of American law, as well as constitutional law, contracts, property, criminal law, and courtroom procedure, are all presented in their historical and intellectual contexts, accessible to the novice but with insight that will inform the expert. Actual cases illuminate each major subject, engaging readers in the legal process and the arguments between real people that make American law an ever-evolving system